Adaptive evolution to a high purine and fat diet of carnivorans revealed by gut microbiomes and host genomes. (26th March 2018) - Zhu, Lifeng; Wu, Qi; Deng, Cao; Zhang, Mengjie; Zhang, Chenglin; Chen, Hua; Lu, Guoqing; Wei, Fuwen
Summary: Carnivorous members of the Carnivora reside at the apex of food chains and consume meat‐only diets, rich in purine, fats and protein. Here, we aimed to identify potential adaptive evolutionary signatures compatible with high purine and fat metabolism based on analysis of host genomes and symbiotic gut microbial metagenomes. We found that the gut microbiomes of carnivorous Carnivora (e.g., Felidae, Canidae) clustered in the same clade, and other clades comprised omnivorous and herbivorous Carnivora (e.g., badgers, bears and pandas). The relative proportions of genes encoding enzymes involved in uric acid degradation were higher in the gut microbiomes of meat‐eating carnivorans than plant‐eating species. Adaptive amino acid substitutions in two enzymes, carnitine O‐palmitoyltransferase 1 (CPT1A) and lipase F (LIPF), which play a role in fat digestion, were identified in Felidae‐Candidae species. Carnivorous carnivorans appear to endure diets high in purines and fats via gut microbiomic and genomic adaptations.